Aspek Hukum Pidana Terhadap Hubungan Kausalitas Pada Tindak Pembiaran Korban Penganiayaan Sehingga Meninggal Dunia - Anak Agung Sagung Laksmi Dewi; Anak Agung Ngurah Adhi Wibisana (Jurnal Interpretasi Hukum, 2025)
Protection of human life is a fundamental principle of criminal law that positions society not merely as passive witnesses, but as legal subjects who have moral and legal obligations to act in emergency situations. Allowing a victim to be abused to the point of death constitutes a form of serious negligence that can legally result in criminal liability, especially when such passivity is part of a chain of cause and effect that worsens the victim's condition. The problem formulation in this study includes: (1) what is the status of society as a legal subject in emergency situations?, and (2) what is the importance of the causal relationship in acts of omission in determining criminal liability?. The analysis was conducted using normative legal methods through legislative approaches, case approaches, and conceptual approaches to assess the legal position of the community, the limits of the duty to act, as well as the relevance of causal relationships in determining whether criminal sanctions are appropriate. The study results show that Article 531 of the Criminal Code establishes a duty of assistance for anyone who witnesses a person in mortal danger, while the element of causality serves as the main basis for determining whether the victim's death can be attributed to the community's passive actions. Omission can be punishable if such inaction factually and normatively contributes to the loss of the victim's chance of survival. This study emphasizes that in emergency situations, the community has an active legal role; the duty to act, protection of life, and proof of causality are important instruments in establishing criminal liability proportionally.